Conjunctival Microbial Flora in Ocular Stevens–Johnson Syndrome Sequelae Patients at a Tertiary Eye Care Center. Issue 8 (August 2016) - Venugopal, Renu; Satpathy, Gita; Sangwan, Sushil; Kapil, Arti; Aron, Neelima; Agarwal, Tushar; Pushker, Neelam; Sharma, Namrata
Abstract : Purpose: To evaluate the conjunctival microbial flora in cases of ocular Stevens–Johnson Syndrome (SJS) in a tertiary eye care center. Methods: This prospective study comprised 176 eyes of 88 patients with ocular SJS compared with 124 eyes of normal subjects. The conjunctival swabs were collected and sent for microbiological analysis for bacterial isolation and antibiotic sensitivity examination. The type of bacteria isolated and its antibiotic sensitivity pattern were studied. Results: Of 176 eyes, 104 (59%) had positive cultures for bacteria in cases of SJS and 16 (12.9%) had positive culture in the control group, the difference being statistically significant ( P = 0.001). In the SJS group, 14 different types of bacterial isolates were identified. The most common isolate was coagulase-negative staphylococci (CNS) (30/104, 28.8%) followed by Corynebacteria species (35/104, 33.6%) and Staphylococcus aureus (19/104, 18.2%). More than 1 bacteria were isolated in 7 eyes (6.7%). Most of the isolates showed resistance to ciprofloxacin with no resistance to gatifloxacin and moxifloxacin. In the control group, only 2 bacteria were isolated, which included CNS (14/16, 87.5%) and Streptococcus pneumoniae (2/16, 12.5%). CNS showed resistance to ciprofloxacin, and S. pneumoniae was resistant to tobramycin and gentamycin. Conclusions: Ocular SJS is associated with alteration of the normal microbial flora residing in the conjunctival sac. The study of which is vital in cases of infection in these eyes with compromised ocular surface. Mixed flora are seen more often in cases of ocular SJS as compared with controls. Abstract : Supplemental Digital Content is Available in the Text.